Risk Factors for Blood Transfusion in Women with Placenta Previa Undergoing Cesarean Delivery: A Retrospective Case-Control Study - Saowapark Chumpathong; Shusee Visalyaputra; Waewdao Sanguanpong; Jantra Tipchai; Benno von Bormann; Saipin Muangman; Pranee Rushatamukayanunt; Suppachai Poolsuppasit (Siriraj Medical Journal, 2015)
Background: Hemorrhage is a leading cause of maternal death. Placenta previa increases risk of massive bleeding, requires massive blood transfusion, and increases incidence of hysterectomy. Objective: To identify risk factors for blood transfusion in Thai women with placenta previa undergoing cesarean section. Methods: This was a retrospective case-control study of patients who had placenta previa and underwent cesarean section during January 2002 to December 2011. A total of 885 singleton pregnancies with placenta previa who delivered by cesarean section after 24 weeks’ gestation were analyzed. Patients with placenta adherence were not included. Results: Of 885 patients studied, 166 patients (18.8%) received blood transfusion. Independent risk factors (odds ratio (OR); 95% confidence interval (CI) for transfusion were preoperative anemia (OR 2.8; 1.8-4.37), history of uterine curettage (OR 1.82; 1.08-3.05), previous cesarean section (OR 2.61; 1.52-4.48), complete placenta previa (OR 3.03; 1.96-4.68), general anesthesia (OR 3.8; 2.53-5.72), and after-hours surgery (OR 1.6; 1.06-2.42). Conclusion: Incidence of blood transfusion in women with placenta previa was 18.8%. Risk factors for blood transfusion were preoperative anemia, history of uterine curettage and/or cesarean section, complete placenta previa, general anesthesia, and after-hours surgery. Identification of these risk factors may alert practitioners to undertake preoperative precautions to avoid massive bleeding.